Two-gaps microwave ion engine and its study by aerodynamic method - I. S. Vavilov; P. S. Yachmenev; V. V. Fedyanin; K. I. Zharikov; P. V. Stepen; A. I. Lukyanchuk; I. A. Kuzmenko (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article contains the authors’ research in the field of jet propulsion systems with low energy consumption of small spacecraft of the class of nanosatellites. The paper presents a microwave ion engine with double acceleration of ionized gas in the gaps formed by the end surfaces of cylindrical resonators. The results of an experimental study of the pressure force of a jet set of ionized gas by the aerodynamic double angle method are presented. A stand for determining the power parameters of week plasmajet is presented. The design of the prototype is presented. The total energy consumption of the prototype is 5 watts, the accelerated gas flow rate is up to 200 km/s, the jet pressure force on the sensing element of the stand is 0,1 μN. The working body of the prototype is nitrogen at a pressure in a vacuum chamber of 18 Pa.